Hospital ethics committees in Israel: structure, function and heterogeneity in the setting of statutory ethics committees. Issue 3 (1st June 2002) - Wenger, N S; Golan, O; Shalev, C; Glick, S
Abstract : Objectives: Hospital ethics committees increasingly affect medical care worldwide, yet there has been little evaluation of these bodies. Israel has the distinction of having ethics committees legally required by a Patients' Rights Act. We studied the development of ethics committees in this legal environment. Design: Cross-sectional national survey of general hospitals to identify all ethics committees and interview of ethics committee chairpersons. Setting: Israel five years after the passage of the Patients' Rights Act. Main measurements: Patients' rights and informal ethics committee structure and function. Results: One-third of general hospitals have an ethics committee, with committees concentrated in larger facilities. Hospitals without committees tended to lack any structure to handle ethics issues. Committees tend to be interdisciplinary and gender-mixed but ethnic mix was poor. Confidentiality is the rule, however, legal liability is a concern. One-third of patients' rights ethics committees never convened and most committees had considered fewer than ten consults. Access to the consultation process and the consultation process itself varied substantially across committees. Some patients' rights ethics committees attempted to solve cases, others only rendered decisions. Informal committees often refused to consider cases within Patients' Rights Act jurisdiction. Conclusions: Despite statutory requirement, many Israeli patients and clinicians do not have access to ethics committees. The scant volume of cases shows serious discrepancies between practice and Patients' Rights Act regulations, suggesting the need for education or revision of the law. Heterogeneity in committee function demonstrates need for substantial improvement.